Prevalence of non-acute ischaemic cardiomyopathy in a Pakistani cohort. Issue 1 (25th March 2019) - Ghazni, Muhammad Salman; Aijaz, Saba; Malik, Rehan; Pathan, Asad Z
Abstract : Heart failure with reduced left ventricular ejection fraction (HFrEF) is a frequently encountered clinical scenario. Coronary angiography (CAG) is usually performed to assess obstructive epicardial coronary artery disease (CAD) and the resultant ischaemia as causes of HFrEF. Objectives: To determine the frequency of obstructive CAD (OCAD) in patients with HFrEF and its independent predictors and outcomes. Methods: Retrospective observational study in Tabba Heart Institute on patients who underwent CAG during the past 4 years. Patients with prior known CAD or revascularisation were excluded. OCAD was defined as per the criteria from Felker et al . Regression modelling was performed to evaluate the predictors of OCAD. Survival was compared between the groups using the log rank test. Results: Out of 2235 patients who underwent CAG, 260 had HFrEF as a primary indication for CAG and, of these, 119 (45.8%) had OCAD. Major predictors of OCAD were age >50 years at presentation (OR 2.0, 95% CI 1.1 to 3.7), presence of chest pain (OR 4.3, 95% CI 2.3 to 8.1), family history of premature CAD (OR 2.8, 95% CI 1.3 to 5.9) and utilisation of non-invasive (NIV) stress testing before CAG (OR 3.6, 95% CI 1.8 to 7.1). Survival was significantly lower (log rank p<0.001) in patients with OCAD with no revascularisation compared with OCAD with revascularisation or those who had non-obstructive CAD, and the latter two groups had comparable survival. Conclusions: OCAD is detected in nearly half of the patients with reduced left ventricular systolic function undergoing CAG. Clinical judgement based on thorough history and use of NIV stress testing can help in appropriate patient selection for this test.